Acute lymphoblastic leukemia in a patient with MonoMAC syndrome/GATA2 haploinsufficiency. Issue 10 (27th May 2016) - Koegel, Ashley K.; Hofmann, Inga; Moffitt, Kristin; Degar, Barbara; Duncan, Christine; Tubman, Venée N.
Abstract: Patients with GATA2 haploinsufficiency have a significant predisposition to developing cytopenias, unique infectious manifestations, and myelodysplastic syndrome/acute myeloid leukemia (MDS/AML). We report a unique case of a patient who presented with B‐cell acute lymphoblastic leukemia (B‐ALL) and was subsequently diagnosed with monocytopenia and mycobacterium avium complex (MonoMAC) syndrome/ GATA2 haploinsufficiency. The development of MDS/AML in patients with GATA2 haploinsufficiency is well described, however, the development of ALL has not been reported in the literature. ALL may be associated with GATA2 haploinsufficiency. Clinicians should be attuned to the features of the MonoMAC syndrome in patients with ALL that would prompt additional testing and alter treatment.